A Study of Serum Uric Acid Level in Patients with Psoriasis at a Tertiary Care Hospital in Eastern Nepal - Pradhan, Manish; Rai, Anjan; Karki, Sunita; Yadav, Rajiv; Yadav, Sanjeev (Journal of Nobel Medical College, 2022)
Background: Meta-analysis has shown that psoriasis is associated with hyperuricemia and its sequel. So this study was done with objective to find out the association of serum uric acid level in patient with psoriasis and its correlation with severity of the disease. Materials and Methods: It was a prospective case control study conducted in the department of Dermatology, Nobel Medical College Teaching Hospital in eastern region of Nepal over a period of one year from Jan 2020 to Dec 2022 after approval of Intuitional review committee on Nobel Medical College Teaching Hospital. The diagnosis of the disease for the cases were done by clinical examination and biopsy when needed. 50 cases and 50 control sample were taken for the study. Psoriasis Area Severity Index was calculated for the cases and serum uric level was measured for both cases and control. Results: The mean serum uric level in psoriatic patients was 6.16 ± 1.64mg/dl with range of 4 to 11 mg/dl and that of control group was 5.39 ± 1.60 mg/dl with the range of 2 to 9mg/dl. Mean serum uric acid level in psoriatic group was significantly higher than in control group with p value of 0.002 and there was positive correlation between severity of psoriasis with serum uric acid level(p=0.001). Conclusion: Psoriasis was associated with hyperuricemia in psoriasis patients.